2009
DOI: 10.1681/asn.2009010011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Nephrin Triggers Its Internalization by Raft-Mediated Endocytosis

Abstract: Proper localization of nephrin determines integrity of the glomerular slit diaphragm. Slit diaphragm proteins assemble into functional signaling complexes on a raft-based platform, but how the trafficking of these proteins coordinates with their signaling function is unknown. Here, we demonstrate that a raft-mediated endocytic (RME) pathway internalizes nephrin. Nephrin internalization was slower with raft-mediated endocytosis than with classic clathrin-mediated endocytosis. Ultrastructurally, the RME pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 44 publications
11
92
0
Order By: Relevance
“…In accordance with our results, the role of PKC␣ in diabetic nephrin endocytosis was confirmed very recently by Tossidou et al (33). It has been recently reported that nephrin traffics via raft-or clathrin-mediated endocytosis (34). From other receptors, it is known that ␤-arrestin2-dependent endocytosis mainly utilizes the clathrin pathway.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, the role of PKC␣ in diabetic nephrin endocytosis was confirmed very recently by Tossidou et al (33). It has been recently reported that nephrin traffics via raft-or clathrin-mediated endocytosis (34). From other receptors, it is known that ␤-arrestin2-dependent endocytosis mainly utilizes the clathrin pathway.…”
Section: Discussionsupporting
confidence: 92%
“…24 Nephrin, a structural component BASIC RESEARCH www.jasn.org of the glomerular slit diaphragm, is a single transmembranespanning receptor and also undergoes endocytosis, which affects slit diaphragm integrity. 22,25,26 In this study, reduction and altered staining patterns of nephrin and podocin would be due to a general defect in a secretory system as a cause of the podocyte disorder. Accumulation of intracellular vesicles in podocytes clearly argues into this direction and does not imply a specific defect in trafficking of slit-diaphragm proteins as a cause of the disease.…”
Section: Discussionmentioning
confidence: 78%
“…Quack et al demonstrated that threonine phosphorylation of nephrin triggers recruitment of ␤-arrestin-2, an adaptor protein known to mediate endocytosis of G protein-coupled receptors (26), which induces nephrin endocytosis (27). Nephrin internalization was also shown to occur via CIN85-mediated ubiquitination (28) and raft-mediated endocytosis (29). So far, disturbances of nephrin endocytosis have been implicated in the context of disease states, for example in high glucose-mediated podocyte injury (27).…”
mentioning
confidence: 99%